Secotrijugins A−D, four highly oxidized and rearranged limonoids from Trichilia sinensis and their anti-inflammatory activity. (January 2023) - Xing, Honghong; Song, Ziteng; Guo, Ruichen; Liu, Feng; An, Lijun; Hu, Ping; Guo, Yuanqiang
Abstract: Four undescribed highly oxidized and rearranged limonoids, secotrijugins A-D, were purified from the leaves and twigs of Trichilia sinensis . Within them, secotrijugin A was characterized as a rare 30-nortrijugin-type limonoid with an unusual cleavage of 1, 14-ether bond, secotrijugins B and C represented new examples with the cleavage of δ -lactone ring D, and secotrijugin D was a rare trijugin-type limonoid with an unusual 2, 6-oxygen bridge. The structures of limonoids were characterized by means of spectroscopic analysis and ECD calculations. The cellular screening revealed that secotrijugin B was the most active against LPS-stimulated NO production in BV-2 cells, which played an anti-inflammatory role by downregulating COX-2 and iNOS protein expression. The further in vivo experiments confirmed that secotrijugin B had strong in vivo anti-inflammatory effect via suppressing NO and ROS generation. Graphical abstract: Four undescribed limonoids, secotrijugins A−D, were purified from Trichilia sinensis . Secotrijugin B was found to be the most active against LPS-induced inflammation in vitro and in vivo experiments. Image 1 Highlights: Four undescribed limonoids were isolated from twigs and leaves of Trichilia sinensis. Secotrijugin B was the most active against LPS-stimulated nitric oxide production. Secotrijugin B down regulated iNOS and COX-2 protein expression. Secotrijugin B had anti-inflammatory effects by suppressing NO and ROS generation.